The relationship between self-control and return investment: Evidence from Indonesia - Suwono, Priyo; Giovanni, Axel; Verawati, Dian Marlina (Diponegoro International Journal of Business, 2023)
Self-control in behavioral economics is a matter of intertemporal choice, namely, consumption time. Human behavior in making economic decisions is determined by wealth and the mental accounting one owns. The number of capital market investors in Indonesia has increased in recent years. In addition to conducting fundamental analysis, investors also need to be able to control themselves to reduce the risk of exposure to bias. This study aims to provide evidence of the role of self-control quality on investment returns. The population of this study was capital market investors on the Indonesia Stock Exchange (IDX), with a sample of 51 investors obtained using a purposive sampling method. The research data is primary data obtained from the questionnaire method and analyzed using cluster analysis and an independent samples t-test. The software tool used for data analysis is SPSS 26. The results of this study provide empirical evidence that the quality of self-control plays a role in the investment returns of capital market investors on the Indonesia Stock Exchange (IDX).